Creating a Tapestry: Motherhood and Womanhood Across Borders - Maätita, Florence (Journal of the Motherhood Initiative for Research and Community Involvement, 2013)
In this essay, I examine three primary threads that connect my own biography with those of my grandmother and my mother. Grandma lived her entire life in a small Mexican village, where she raised five children without much help from her family or her husband. Mama, the youngest of Grandma’s children, left this village before her twentieth birthday and immigrated to the US, where she raised three children. I, Mama’s youngest child and only daughter, left her home and found a home in academia. As I illustrate, each of us managed difficult decisions, often in the face of our family’s expectations of us. Our ideas of what constitutes “home” entail geographic place, conceptual space and notions of self-empowerment. Moreover, our biographies highlight varying expressions of motherhood, each of which is complex in its own right. While it is easy to point out how our lives are different, these stories highlight the need to acknowledge how each thread in our family story relates to each other.